A look at the life of Sheikh Hussein Najaf Tabrizi Najafi: The poet jurist and the study of his poetry - Bafrani, Reza (Al-Adab Journal, 2024)
Poems are of great importance in recording many important historical events and facts. They said in the past: poetry is the Arab Divan, and the poets recorded in it their exploits, their days, and their glory. And there is no doubt that Allah has pointed out in the Holy Book to this tribe - the poets - and identified them with the attributes of the good and others of the bad nature. Family of prophets encouraged their Shiites and lovers to write poetry about them, peace be upon them, and many hadiths were received from them urging this matter with the goodness and reward it brings. Therefore, many people paid attention to the poetry collections of the Prophet’s family, peace be upon them, including the nation’s jurists, as they paid great attention to epistolary poetry. To preserve the exploits of the Prophet and his family, peace be upon them, and to perpetuate their memory, Sheikh Al-Kulayni has a book, “What Poetry Has Been Said about the family of prophets,” and Sheikh Al-Mufid has a book, “Mas’a’il Al-Nazam.” There are many scholars and jurists who, in addition to their religious books, have written a book of poetry or composed poetry about the family of prophets, peace be upon them for love of them. Among them is Sheikh Hussein Najaf Al-Tabrizi Al-Najafi, who was motivated by pure love and pure adoration for them, peace be upon them, to compose a collection of poetry that he wrote with the ink of the heart and the water of the eyes for them. What is important to us in this article, after we have outlined a summary of the poet’s life, is to shed light on his scientific and practical status and the artistic and objective characteristics of his poetry.